Pemodelan Arsitektur Sistem Informasi untuk Mendukung Aktivitas Akademik di STIMIKOM Stella Maris Sumba - Yulius Nahak Tetik; Wing Wahyu Winarno; Eko Pramono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Information technology and information systems are a very fundamental requirement in supporting business functions in an organization or company, whether government or private. Amid the rapid development of information technology, universities are challenged to implement information technology and information systems that can facilitate and accelerate services, both to students, lecturers and the general public in terms of obtaining information. In developing information systems, there needs to be careful planning for the short, medium and long term so that the system that has been built can continue to be developed together with the construction of a new system. Enterprise Architecture Planning is a methodology that can be used to build a structured system architecture starting from planning to the implementation planning stage. In this journal, we will discuss the use of Enterprise Architecture Planning in creating information system architecture to support academic activities in the form of data architecture, applications and technology